Real-time visual determination of the flux of hydrogen sulphide using a hollow-channel paper electrode1. Issue 74 (25th September 2015) - Li, Li; Zhang, Yan; Liu, Fang; Su, Min; Liang, Linlin; Ge, Shenguang; Yu, Jinghua
<x xml:space="preserve">Abstract</x> A novel 3D microfluidic paper-based turn-on electrochemiluminescence origami cyto-device with hollow channels is developed and applied for real-time visual determination of H2S released from multiple cancer cells for the first time.